VISUALISASI KEARIFAN LOKAL PADA INDONESIA BAGUS NET TV EPISODE SUNGAI UTIK MASYARAKAT DAYAK IBAN - Ridho, Alfio; Sjafi’i, Achmad (Seni Media Rekam ISI Surakarta, 2015)
Local wisdom is a dialectic results of society in responding their surrounding conditions. The local wisdom visualized television programme of Indonesia Bagus in NET TV especially the episode of Sungai Utik Masyarakat Dayak Iban through the shooting techniques. The techniques consist of resolution (image size), angle, and camera moving. The diversity of shooting techniques in the Indonesia Bagus programme actually have values to show to audiences by director programme.Keywords: Visualization, local wisdom, and shooting techniques